Author Correction: SciPy 1.0: fundamental algorithms for scientific computing in Python - Virtanen, Pauli; Gommers, Ralf; Oliphant, Travis E; Haberland, Matt; Reddy, Tyler; Cournapeau, David; Burovski, Evgeni; Peterson, Pearu; Weckesser, Warren; Bright, Jonathan; van der Walt, Stéfan J; Brett, Matthew; et al. (Nature methods, 2020)
An amendment to this paper has been published and can be accessed via a link at the top of the paper.